2018
DOI: 10.1002/qua.25882
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on the charge transfer properties of Graphene quantum dot based interfaces

Abstract: Graphene quantum dots (GQD) are interesting materials due to the confined sizes which allow to exploit their optoelectronic properties, especially when they interface with organic molecules through physisorption. In particular, when interfaces are formed, charge transfer (CT) processes can occur, in which electrons can flow either from the GQD to the absorbed molecule, or vice versa. These processes are accessible by modeling and computational analysis. Yet, the presence of different environments can strongly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…As depicted in Figure 46, the quantum conjugation effect is most relevant for systems with a certain degree of order, like GQDs or CNDs, and it is largely reported in simulations considering g r a p h e n e l a y e r s o r P A H s o f i n c r e a s i n g size. 26,27,78,85,236,30,32,34,36,39,44,46,60 In the case of disordered systems, such as the amorphous CNDs considered by Margraf, 79 the same trend is reported but with the red-shift proportional to the diameter of the nanoparticle. The authors assigned a relevant role in determining the observed behavior to the structure of the surface where also the sp 2 planar island can be formed as a consequence of the relaxing of the geometrical constraints on the surface atoms.…”
Section: Remarks On the Optical Properties Of Cndsmentioning
confidence: 60%
See 1 more Smart Citation
“…As depicted in Figure 46, the quantum conjugation effect is most relevant for systems with a certain degree of order, like GQDs or CNDs, and it is largely reported in simulations considering g r a p h e n e l a y e r s o r P A H s o f i n c r e a s i n g size. 26,27,78,85,236,30,32,34,36,39,44,46,60 In the case of disordered systems, such as the amorphous CNDs considered by Margraf, 79 the same trend is reported but with the red-shift proportional to the diameter of the nanoparticle. The authors assigned a relevant role in determining the observed behavior to the structure of the surface where also the sp 2 planar island can be formed as a consequence of the relaxing of the geometrical constraints on the surface atoms.…”
Section: Remarks On the Optical Properties Of Cndsmentioning
confidence: 60%
“…It should be noted that the relevant size is the extension of the sp 2 graphene domain rather than the overall size of the nanoparticle. As depicted in Figure , the quantum conjugation effect is most relevant for systems with a certain degree of order, like GQDs or CNDs, and it is largely reported in simulations considering graphene layers or PAHs of increasing size. ,,,,,,,,,,,, …”
Section: Computational Studies Of Cndsmentioning
confidence: 97%
“…The key advantage of GQDs as chromophores for light energy harvesting is their extremely high thermal and photostability, thanks to the rigid carbon frameworks with strong aromatic stabilization and delocalization of π-electrons over the planar cores [22]. Furthermore, GQDs can also be coupled or even fused with other organic chromophores (such as small molecule organic semiconductors (SMOSs)), inducing unique optoelectronic properties, such as broad absorbance and white light emission [23,24]. GQDs show great promise due to their high light absorption coefficient and luminescence, chemical stability, low photo-bleaching, efficient dispersibility in solvents for solution processing, low environmental impact and moderate costs of production [33].…”
Section: D Materialsmentioning
confidence: 99%
“…8,9 The formation of an interface between GQDs and small organic molecules can lead to functional materials, whose optoelectronic properties can be easily tuned by incorporating changes within the molecules. [10][11][12][13] GQDs are applied to a number of applications such as solar cells, [14][15][16][17] light-emitting diodes [18][19][20][21] and supercapacitors. [22][23][24] Moreover, their low toxicity and biocompatibility enable the use of these materials in medical bioimaging 25 and drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%